Exploring the academic assessment experiences of post-secondary Pakistani Students with learning disabilities and challenges faced by their parents and teachers / Shazia Nasir - Nasir, Shazia (2023)
Academic assessments in schools are important because the results generally indicate the level of students’ knowledge, skills, and understanding. The strategies for giving assessments may not be suitable for students with Learning Disabilities (LD) who have different kinds of mental capabilities and emotional stress compared to their normal peers. In Pakistan, there is a significant paucity in the literature regarding the academic assessment experiences of students with learning disabilities. This phenomenological research focused on exploring the academic assessment experiences of post-secondary Pakistani students with learning disabilities (LD) and the challenges their parents and teachers faced. Semi-structured interviews and focus group discussions were conducted with five students with LD (aged 17-21 years) from private schools/colleges, their parents, and teachers. Major themes that emerged from a thematic analysis were self-perception, barriers to academic achievements, lived experiences, parenting challenges, support from academia, effective teachers and their challenges, as well as academic support. The findings revealed that a robust system of assessment is required for students with LD. Majority of the LD students expressed that they need support from their parents, teachers, peers, and school/college administration. The findings also indicated that these students are at a higher risk of anxiety if they lacked support. This is because the exams cause anxiety, and the fear of failing prevents them from properly concentrating on their subjects. On the other hand, the results from parent interviews indicated that parents of students with LD also go through a lot of emotional and financial stress. They were not satisfied with the arrangements made before or during examinations by the school administration, which results in low academic progress of their children. The study argued that a much greater responsibility for assessing students with LD is on the teachers. Due to their comprehensiveness, the results of this study may contribute to the existing literature and be helpful to educators, especially the policy makers in Pakistan in creating more awareness about the academic and social environments of students with LD. The findings can be further explored through interviewing students with other specific LDs like autism, non-verbal LD, and oral/written LD.